Environmental situation of the "Antonio Maceo" Base Business Unit of the Granma poultry company (REDEL. Revista Granmense de Desarrollo Local, 2021)
The research was carried out in the “Antonio Maceo Grajales” Base Business Unit belonging to the Granma Avícola Company, with the aim of determining the environmental situation of that entity and designing measures that minimize the environmental impacts generated by the UEB. In obtaining the information, techniques and methods of the theoretical and empirical level were used, such as observation, interviews and surveys, guaranteeing the veracity of the information. The procedure proposed for social studies in finite or known populations was applied to the determined sample. Of the total universe of 74 workers in the UEB, the sample calculated was 63. The type of sampling carried out was stratified random with a confidence level of 5% (α = 0.05) and a precision of 0.05, with fixation to the size of the stratum. The study was complemented with the criteria of the people of the community in the immediate environment, with 428 inhabitants, of them 256 women and 176 men. The aspects that most affect poultry activity from an environmental point of view were worked on Failure to comply with biosecurity measures, with an emphasis on poor management of wastes, which constitute a potential danger to birds, workers and the community surrounding the facility. Generated environmental problems (soil, air and water pollution) were identified in the UEB that affect the farm itself and its surroundings, and there is a need to implement actions that minimize existing environmental impacts.
Keywords: environmental impacts; biosecurity; waste management; actions